The suitability of apricot for dried fruit production by the combined technology - Rahović Dragan D. (University of Belgrade - Faculty of Agriculture, Belgrade, 2021)
The apricot is considered as one of the most delicious temperate fruit, a highly appreciated stone fruit and a valuable raw material for processing. The Republic of Serbia is one of the leading apricot producers in Southeast Europe, but the assortment is limited by a small number of cultivars harvested, mostly in the ripening season of "Magyar kajszi". In order to introduce the most suitable cultivars in the production, having high yield and high quality for consumption and various forms of processing, introduced and domestic cultivars have been intensively studied. In Serbia, apricots are mostly marketed fresh and processed for jams and spirits, but demand for high-quality dried fruits is increasing. To preserve the nutritional and sensory quality of fresh apricots, choosing the best drying technique is significant, and the most preferred technique is the reduction of moisture through convective drying. The aim of the paper was to compare the potential of the apricot cultivars "Magyar kajszi", "Novosadska rodna", "NS-4" and "NS-6" for dried fruit production by two-phase technology - combined osmotic and convective drying, as well as the profitability of apricot drying on small family farms. Cultivars "NS-4" and "Novosadska rodna" were found to be suitable for combined drying technology. The highest score in the sensory evaluation of the dried apricots was given to "NS-4", and then to "Novosadska rodna". The results indicate that the combined osmotic and convective drying of apricot rather than selling fresh fruits can be a profitable and important added value tool for small family farms.